Pengaruh Pengembangan Sumber Daya Manusia, Kepemimpinan Dan Budaya Organisasi Terhadap Kepuasan Anggota Organisasi (Studi Pada DPM Universitas Islam Malang) - Nailatul Faidiyah; Budi Wahono; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This research seeks to examine the effect of human resource development, leadership, and organizational culture on the satisfaction level of members within the Student Representative Council (DPM) at the Islamic University of Malang. The phenomenon of psychological degradation, such as burnout and declining motivation in student organizations, serves as the background for the urgency of this research. This study employs a quantitative causal-associative approach with a census method (saturated sampling) involving 68 active members from the University and Faculty DPM. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression techniques. The simultaneous results indicate that the three independent variables significantly influence member satisfaction, contributing 22.7% to the variance. Partially, leadership and organizational culture have a positive and significant impact on member satisfaction. However, human resource development was found to have no significant effect on member satisfaction within the DPM Unisma environment. These findings suggest that member satisfaction in student organizations is more determined by managerial styles and the collective value climate rather than existing formal training programs. Organizations are advised to conduct an in-depth evaluation of the relevance of competence development programs to better align with the actual needs of their members. Keywords:HR Development, Leadership, Organizational Culture, Member Satisfaction, DPM Unisma.